Satellite galaxies in groups in the CIELO Project I: Gas removal from galaxies and its re-distribution in the intragroup medium - Rodríguez Moncada, Silvio Ribamar (2022)
We study the impact of the environment on galaxies as they fall in and orbit in the potential well of a Local Group (LG) analogue, following them with high cadence. The analysis is performed on eight disc satellite galaxies from the CIELO suite of hydrodynamical simulations. All galaxies have stellar masses within the range [10 8.1 -109.56 ] M⊙h-1. We measure tidal torques, ram pressure, and specific star formation rates (sSFRs) as a function of time, and correlate them with the amount of gas lost by satellites along their orbits. Stronger removal episodes occur when the disc plane is oriented perpendicular to the direction of motion. More than one peripassage is required to significantly modify the orientations of the discs with respect to the orbital plane. The gas removed during the interaction with the central galaxies may also be found opposite to the direction of motion, depending on the orbital configuration. Satellites are not totally quenched when the galaxies reach their first peripassage and continue forming about 10 per cent of the final stellar mass after this event. The fraction of removed gas is found to be the product of the joint action of tidal torque and ram pressure, which can also trigger new star formation activity and subsequent supernova feedback.